Impact of IL-2 on Treatment Tolerance in Patients With High-Risk Neuroblastoma Treated With Dinutuximab Beta-Based Immunotherapy - Cicek, Filiz; Troschke-Meurer, Sascha; Ceylan, Kiraz; Jahns, Luciana J.; Zumpe, Maxi; Siebert, Nikolai; Ehlert, Karoline; Lode, Holger N. (Frontiers in Pediatrics, 2020)
Patients (pts) with high-risk neuroblastoma (NB) treated with continuous long-term infusion (LTI) of anti-GD2 antibody (Ab) dinutuximab beta (DB) in combination with IL-2 show an acceptable safety profile. Here, we compared treatment tolerance with and without IL-2. Ninety-nine pts with high-risk NB received up to five cycles of DB given as LTI (10 mg/m2/d, 100 mg/m2; per cycle) without IL-2 (46 pts; regimen A) and with IL-2 (53 pts; regimen B; 6x106 IU/m2/d; 60x106 IU/m2/cycle) in a single center compassionate use program. Clinical parameters (body temperature, vital signs, Lansky performance score), laboratory values (C-reactive protein, IFN-γ, IL-6 and IL-18 (cycle 1)) and requirement of i.v. co-medication (e.g. morphine, metamizole) were systematically assessed and used to define potential “outpatient candidates”. Pts showed higher levels of body temperature and CRP in regimen A compared to B. However, IL-6 serum concentrations were similar in pts of both cohorts in the first cycle. Pts receiving regimen A showed a shorter time to achieve normal vital parameters and required less co-medication compared to pts in regimen B that resulted in a shorter median time period to discharge and to achieve a potential outpatient status (6d regimen A and 3-5d regimen B after start of Ab-infusion, respectively). This study shows that omitting IL-2 from immunotherapy with DB allows reduced co-medication and hospitalization time and therefore results in improved quality of life in pts with high-risk NB.